2019
DOI: 10.3390/w11050907
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Unsteady Flow Events on Bedload Transport: A Review of Laboratory Experiments

Abstract: Recent advances in understanding bedload transport under unsteady flow conditions are presented, with a particular emphasis on laboratory experiments. The contribution of laboratory studies to the explanation of key processes of sediment transport observed in alluvial rivers, ephemeral streams, and river reaches below a dam is demonstrated, primarily focusing on bedload transport in gravel-bed streams. The state of current knowledge on the impact of flow properties (unsteady flow hydrograph shape and duration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Similarities between riprap sloping structures and river training structures exist, highlighting the need for in-detail research, as flow overtopping and additional contraction scour can significantly reduce the bridge safety under more frequent flood events driven by climate change. Although many researchers have investigated the effects of flow events on bedload transport and scour processes in laboratory studies [83,85,[139][140][141][142] (for a systemic review, see also [96]), studies with field measurements are still rare [39,40], especially those with continuously measured flow waves and associated scour depths [95,143].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarities between riprap sloping structures and river training structures exist, highlighting the need for in-detail research, as flow overtopping and additional contraction scour can significantly reduce the bridge safety under more frequent flood events driven by climate change. Although many researchers have investigated the effects of flow events on bedload transport and scour processes in laboratory studies [83,85,[139][140][141][142] (for a systemic review, see also [96]), studies with field measurements are still rare [39,40], especially those with continuously measured flow waves and associated scour depths [95,143].…”
Section: Discussionmentioning
confidence: 99%
“…However, these formulae were mostly developed for steady-state flow conditions or adapted to unsteady conditions using various approaches, such as superposition of the hydrograph as a sequence of steady-state discharge steps [89][90][91], introducing a mathematical function for form of the hydrograph [92], or defining a dimensionless effective flow [93,94]. Apart from the fact that real-time field measurements are rarely available at high turbidity during a flood, the main challenge in studying the effects of flow characteristics, i.e., unsteady flow characteristics and the influence of multiple flood waves [95] on bedload transport and the scour process, is to separate the effects of flow conditions from the effects of bed material properties and sediment supply conditions [96]. It can be concluded that in future research it is necessary to investigate the effects on the development of maximum scour depth not only during a single flood event and the associated flood wave characteristics, but also previous flood events should be considered.…”
Section: Variables Governing the Scour Processmentioning
confidence: 99%
“…The second current points out that there is no memory effect of antecedent flood events, instead sediment composition is the major factor of fluvial system memory [83,84]. The majority of these conclusions are drawn based on lab experiments, whereas in nature the cumulated effects of several control factors can annul the influence of antecedent floods, as was the case with the 2007 flood events on Trotuș River.…”
Section: V1mentioning
confidence: 99%
“…Common classes of sediment hysteresis are (1) clockwise, indicating a greater sediment transport rate on the rising limb of hydrographs; (2) counterclockwise, indicating a greater sediment transport rate on the falling limb of hydrographs; (3) single value plus a loop, a combination of 1 and either 2 or 3; and (4) figure eight, a combination of 2 and 3. Although these classes were originally characterized for suspended sediment concentrations and discharge relations (Williams, 1989), they have also been observed for bedload transport under unsteady flow conditions in both field (Reid et al, 1985;Sidle, 1988;Kuhnle, 1992;Hassan and Church, 2001) and laboratory studies (Lee et al, 2004;Mao, 2012;Humphries et al, 2012;Waters and Curran, 2015;Wang et al, 2015;Mrokowska et al, 2016;Mrokowska and Rowinski, 2019). Clockwise hysteresis has been attributed to 'a lag in the formation' of roughness elements to arrest sediment transport (Kuhnle, 1992) or to an initially loose bed due to antecedent floods (Reid et al, 1985).…”
Section: Introductionmentioning
confidence: 99%